Effectiveness Method Jarimatika To Ability Counting Multiplication Participant Class III students at SDN 1 Lungbenda Subdistrict Palimanan Cirebon Regency - Zaqiyatul Fakhiroh; Bambang Firmansyah; Shulkhah Shulkhah (PT. Pusmedia Group Indonesia, 2023)
The study in the background behind by the low ability counting multiplication participant education and methods ongoing learning _ conventional ( memorization ) is used in the learning process . Objective study This is For know ability counting multiplication participant educate before use method jarimatics , knowing ability counting multiplication participant educate after use method Mathematics , and knowing difference ability counting multiplication participant educate before and after use method Jarimatika . Method research used _ is method quantitative type experiment with design used pre - experiment as for the model namely one group pretest-posttest. Population study This is 20 participants consisting of students of 12 men and 8 women . Retrieval technique samples in research This is saturated sampling which all participant educate class III as many as 20 students become sample study . Ability counting multiplication participant educate class III of SD Negeri 1 Lungbenda after use method Jarimatika categorized as high , p This based on percentages score mark amounting to 78.9% with the class average score is 78.89 with total of 20 participants educate . There is significant difference _ between ability counting multiplication participant educate class III of SD Negeri 1 Lungbenda Subdistrict Palimanan Cirebon Regency before use method jarimatics and after use method Jarimatika . This matter proven through testing hypothesis carried out through the Paired sample T-Test test, it was proven that Ha was accepted and H0 was rejected . with results thitng > ttable that is amounting to 5,666 > 1,724 as well mark significance of more than 0.000 small from 0.05 (0.000 < 0.05). So , method Jarimatika be one _ alternative method effective learning _ used For Study multiplication to make more easy Because there is difference results Study before and after apply method This . However with notes practice in a way continously method Jarmatics so that it doesn't forget method use his finger